The Alden Amos big book of handspinning : [being a compendium of information, advice, and opinions on the noble art & craft] - Amos, Alden; Gaustad, Stephenie (Loveland, CO : Interweave Press, 2001)
Alden Amos shares his deep knowledge of wheel mechanics, spinning fibers, wheel construction, and yarn, as well as a wealth of spinning history and traditions. Every aspect of handspinning is explored, including dissolving lanolin, washing fleece, rotating wheel position, and choosing types of wool. Also discussed are various hand positions, which can result in everything from smooth, fine thread to funky, bulky yarn.
Includes bibliographical references (pages 474-489) and index.
Keywords: Hand spinning; Hand spinning; Spinning